Children in the Streets: Film as Movement-Translation Device - Donoso, Catalina (Universidad de Chile. Instituto de la Comunicación e Imagen, 2011)
This work examines the filmic representation of homeless children transiting the urban space and cinematographic apparatus as a translator of that movement. The analysis focuses in two Latin American works: Valparaíso mi amor by Aldo Francia and Crónica de un niño solo by Leonardo Favio, proposing them as examples to depict the relation between the camera as a machine of passivity and confinement and narrative and syntactic decisions developed by each film.